2014
DOI: 10.5465/ambpp.2014.17696abstract
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Great Divide Between Theoretical and Empirical Management Research

Abstract: Management research places a great premium on theory development. Despite this emphasis, concerns have been expressed regarding the extent to which management theories are tested in empirical research. This article reviews evidence concerning the connections between theoretical and empirical management research and reports an investigation that examines the correspondence between the propositions presented in 20 highly cited theoretical articles and the hypotheses stated in 361 empirical articles that cite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…Yet, ironically, 90% of theories/models published in AMR are never tested (Kacmar & Whitfield, 2000). More recent evidence, looking at the top-cited articles in AMR confirms that almost none of the theoretical propositions are directly tested in empirical research (Edwards, Berry, & Stewart, 2016). It is rather odd that we have "theory envy" when the best theories our field produces are never tested.…”
Section: Disease 3: Theorrheamentioning
confidence: 99%
“…Yet, ironically, 90% of theories/models published in AMR are never tested (Kacmar & Whitfield, 2000). More recent evidence, looking at the top-cited articles in AMR confirms that almost none of the theoretical propositions are directly tested in empirical research (Edwards, Berry, & Stewart, 2016). It is rather odd that we have "theory envy" when the best theories our field produces are never tested.…”
Section: Disease 3: Theorrheamentioning
confidence: 99%
“…Over time, however, we seem to have forgotten the meaning and purpose of theory. The result is a field that can produce the findings of Edwards et al (2013); Leavitt et al (2010); Kacmar and Whitfield (2000), and O'Boyle et al (in press). None of the changes that are needed are terribly difficult to implement, but they do require the will of the small number of people who determine the editorial policies of our top journals.…”
Section: Resultsmentioning
confidence: 99%
“…As was mentioned earlier, Edwards et al () have found that AMR models are very rarely tested. This is not to say that many of the individual linkages in such models are not tested in some fashion, but it is very rare for a study to provide a comprehensive and critical test of an AMR model.…”
Section: What Needs To Happen?mentioning
confidence: 96%
See 1 more Smart Citation
“…Few of these offered theories are ever tested even once. This is evident by Edwards, Berry, and Kay's (2014) investigation showing that most theories proposed in Academy of Management Review (AMR) were never tested in subsequent publications. Similarly, Kacmar and Whitfield (2000) observed that of those articles citing a paper published in AMR, the majority did not test the hypotheses proposed in the original article.…”
mentioning
confidence: 99%